The alteration and role of glycoconjugates in Alzheimer’s disease - Kang, Yue; Zhang, Qian; Xu, Silu; Yu, Yue (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD) is a prevalent neurodegenerative disorder characterized by abnormal protein deposition. With an alarming 30 million people affected worldwide, AD poses a significant public health concern. While inhibiting key enzymes such as βsite amyloid precursor protein-cleaving enzyme 1 and γ-secretase or enhancing amyloid-β clearance, has been considered the reasonable strategy for AD treatment, their efficacy has been compromised by ineffectiveness. Furthermore, our understanding of AD pathogenesis remains incomplete. Normal aging is associated with a decline in glucose uptake in the brain, a process exacerbated in patients with AD, leading to significant impairment of a critical post-translational modification: glycosylation. Glycosylation, a finely regulated mechanism of intracellular secondary protein processing, plays a pivotal role in regulating essential functions such as synaptogenesis, neurogenesis, axon guidance, as well as learning and memory within the central nervous system. Advanced glycomic analysis has unveiled that abnormal glycosylation of key AD-related proteins closely correlates with the onset and progression of the disease. In this context, we aimed to delve into the intricate role and underlying mechanisms of glycosylation in the etiopathology and pathogenesis of AD.By highlighting the potential of targeting glycosylation as a promising and alternative therapeutic avenue for managing AD, we strive to contribute to the advancement of treatment strategies for this debilitating condition.